Analisis Perkembangan Dan Pelanggaran Hak Asasi Manusia (HAM) Di Indonesia - Faturohman Faturohman; Samsul Anwar; Yulliastuti Yulliastuti (Jurnal Hukum dan Sosial Politik, 2024)
Development is a process in which a condition, situation, or entity experiences change or progress from one state to another that is better or more advanced. In a broader context, development can cover various fields, such as economic, technological, social, cultural and political. Development is often associated with positive progress or growth. Development can also refer to a more general process of change, including changes in people's thoughts, views, and values. Development refers to the physical, mental, emotional, and social growth that occurs throughout a person's life cycle. Violations are actions or behavior that violate established rules, laws, norms or codes of ethics. Violation often refers to actions that violate laws or regulations imposed by the government. This can include actions such as theft, violence, fraud, drug abuse, and so on. Violations of the law can impact individuals, groups, or society as a whole and can result in legal consequences, such as incarceration, fines, or other penalties. Violations reflect non-compliance or violation of established standards, and often result in negative impacts, both for the individual who violates and for other people or society as a whole. In Indonesia, there are regulations regarding Human Rights (HAM), which have been implemented in established laws and regulations. In Indonesia, Human Rights (HAM) can be regulated in various laws and regulations such as: 1956 Constitution, articles 18-34 concerning Human Rights (HAM). These articles can guarantee basic rights such as the right to life, freedom, justice, legal protection, religious freedom, and the right to get a job. Law Number 39 of 1999 concerning Human Rights (HAM). This law is a regulation that specifically regulates human rights in Indonesia. This law states the Indonesian government's commitment to Human Rights (HAM) and establishes the basic principles and mechanisms for protecting Human Rights (HAM). And also, Law Number 26 of 2000 concerning Human Rights Courts (HAM), which regulates law enforcement against human rights violations in Indonesia, including the establishment of a Human Rights Court as a special law enforcement institution that examines and adjudicates cases of violations. HAM. The development and violations of Human Rights (HAM) in Indonesia have a significant impact on society, the government and the country as a whole. The following is the impact, namely the protection and promotion of individual rights, where the development of Human Rights (HAM) has a positive impact by ensuring that individual basic rights are respected and promoted. This includes the right to freedom of opinion, freedom of religion, the right to legal protection, economic, social and cultural rights. This development strengthens democracy and the welfare of society as a whole